Sosialisasi Pencegahan Stunting Terhadap Ibu Hamil dan Ibu yang Memiliki Anak Usia 0-3 Tahun di Desa Tambak Sarinah - Istiqamah; Arnida Tika, Nanda Safitri Esti Chomah, Ahmad Baihaki, Abdurrahman Nawwar, Mayda Riyanti Asyharini, (Borneo Community Development, 2024)
Stunting is a chronic nutritional issue experienced by toddlers, characterized by shorter stature compared to their peers of the same age. Stunting is caused by various factors, including socioeconomic conditions, maternal nutritional status during pregnancy, illnesses experienced by infants, and insufficient nutritional intake during infancy. This study is observational and involves interviews conducted in Tambak Sarinah Village, Kurau Subdistrict, Tanah Laut Regency. Due to the lack of knowledge among village residents about stunting, students from the University of Muhammadiyah Banjarmasin collaborated with the Tambak Sarinah Village government to conduct socialization and prevention activities regarding stunting. These activities include promoting prevention methods and appropriate stunting management. The aim of these activities, as well as the target set by the KKN students, is to generate high enthusiasm among residents so that the educational efforts run smoothly. As a result of these activities, villagers are no longer unfamiliar with the issue and are informed about how to prevent stunting.